Persistent double strand break accumulation does not precede cell death in an olaparib-sensitive BRCA-deficient colorectal cancer cell model - Paviolo, Natalia Soledad (2019)
The poly (adenosine diphosphate (ADP)-ribosyl) polymerase inhibitors (PARPi) selectively kill cancer cells with BRCA1 or BRCA2 (BRCA)-mutations. It has been proposed that cell death induction after PARPi depends on unrepaired double strand breaks (DSBs) that accumulate due to the homologous recombination deficiency of BRCA-mutated cells. Such accumulation of DSBs is inferred mainly from the high levels of DNA damage markers like phosphorylated histone H2AX. Herein, we developed a model of isogenic cell lines to show that depletion of BRCA causes PARPi-triggered cell death, replication stress (phosphorylated-H2AX and 53BP1 foci), and genomic instability. However, persistent DSBs accumulation was not detected under the same experimental conditions. Hence, at least in this cellular model, the trigger for cell death in PARPi-treated BRCA-depleted samples is not the accumulation of unrepaired DSBs. Instead, cell death better correlates with a rapid and aberrant resolution of DSBs by error-prone pathways that leads to severe chromosomic aberrations. Therefore, our results suggest that in PARPi-treated BRCA-deficient cells, chromosome aberrations may dually trigger both genomic instability and cell death.